Pelaksanaan Layanan Informasi dalam Meningkatkan Self Management Siswa dalam Belajar di SMP Budi Agung Medan - Fadil Abdillah; Alfin Siregar; Ali Daud Hasibuan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
A guidance and counseling teacher or supervisor is responsible for his students at the school, especially regarding students' lack of discipline towards school regulations, the guidance and counseling teacher must provide services to students who often make mistakes against themselves, therefore the aim of the guidance and counseling teacher there is to provide information services in improving Self Management of students there, not just for students who discipline, guidance and counseling teachers provide information services to all students at school to form behavior that is in accordance with what has been arranged to achieve something good and expected at Budi Agung Middle School Medan. The type of research that researchers use is qualitative research or field research. In this research, researchers conducted interviews with guidance and counseling teachers as key informants. And 8 students who experienced disciplinary problems as data triangulation, as well as the head of student affairs, and the student's homeroom teacher. The results of the research found that the basic consideration for guidance and counseling teachers in providing information services is to develop students' disciplinary behavior because there are still students who have less disciplined behavior such as often coming late, skipping classes, not doing assignments, often going out during class hours and not dressing neatly. The time used by guidance and counseling teachers is during special guidance and counseling lessons every week and can be used during free hours or when other subject teachers are not available. And the duration of time used by the guidance and counseling teachers themselves is approximately 30 minutes to carry out information services. The places where it is implemented are in the classroom, outside the classroom, in the hall and in applications such as Google Met and Zoom. Information service materials to develop student discipline behavior include self-discipline, clean and healthy lifestyle, and leadership spirit. At the time of implementation, students who had received information services were very active in paying attention to what was conveyed and enthusiastic in giving their opinions and understanding what was conveyed by the guidance and counseling teacher regarding the services delivered after being given the information service. If there were still students who had not changed, then the guidance and counseling teacher would individual counseling services to the student. After providing individual services, if the student has not changed, the guidance and counseling teacher will hand the student over to the head of student affairs for further follow-up.